2009
DOI: 10.3858/emm.2009.41.4.025
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the caveolin-3 localization to caveolae and STAT3 to mitochondria by catecholamine-induced cardiac hypertrophy in H9c2 cardiomyoblasts

Abstract: We investigated the effect of phenylephrine (PE)-and isoproterenol (ISO)-induced cardiac hypertrophy on subcellular localization and expression of caveolin-3 and STAT3 in H9c2 cardiomyoblast cells. Caveolin-3 localization to plasma membrane was attenuated and localization of caveolin-3 to caveolae in the plasma membrane was 24.3% reduced by the catecholamineinduced hypertrophy. STAT3 and phospho-STAT3 were up-regulated but verapamil and cyclosporin A synergistically decreased the STAT3 and phospho-STAT3 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Unlike these receptors, β 2 ARs can be confined into the caveolae, where they are coupled with G i protein, thus impairing cAMP production and activating a pro-survival pathway 33,[35][36][37] . Chronic βAR over-stimulation also induces the downregulation of caveolin-3 38 , the structural component of caveolae, allowing β 2 AR to move out of caveolae where they mediate the same effects of β 1 AR 33,35,39 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unlike these receptors, β 2 ARs can be confined into the caveolae, where they are coupled with G i protein, thus impairing cAMP production and activating a pro-survival pathway 33,[35][36][37] . Chronic βAR over-stimulation also induces the downregulation of caveolin-3 38 , the structural component of caveolae, allowing β 2 AR to move out of caveolae where they mediate the same effects of β 1 AR 33,35,39 .…”
Section: Discussionmentioning
confidence: 97%
“…ISO administration was reported to reduce caveolin-3 expression and caveolae density 33,38,[41][42][43] .…”
Section: Discussionmentioning
confidence: 98%
“…For instance, STAT3 has been found to interact with GRIM-19, a known component of mitochondrial complex I (17,18) and to regulate mitochondrial complex function of the respiratory chain in primary pro-B lymphocytes and the heart (19,20). More recently, Jeong et al (21) reported that catecholamine-induced hypertrophy modulates the expression and activation of STAT3 in mitochondria of cardiomyocytes. In light of these and related observations, an understanding of the role for SIRT1-STAT3 connection in mitochondria respiration is important.…”
mentioning
confidence: 98%
“…The features of cardiac hypertrophy include enlarged cardiomyocyte size, increased protein synthesis, elevated fetal gene atrial natriuretic peptide, brain natriuretic peptide (BNP) and β-myosin heavy chain (β-MHC) expression, and abnormal sarcomeric organization, as well as heightened expression of fibronectin. There are numerous cell signaling pathways associated with cardiac hypertrophy and cardiac failure, including signal transducer and activator of transcription 3, Akt, extracellular signal-regulated kinase (ERK)1/2 and liver kinase B1/5' AMP-activated protein kinase (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…When the cells reached 70-80% confluence, they were passaged according to a 1:2 proportion and the medium was changed every 2 days. Cells were seeded into a 35-mm dish at a density of 1x10 5 . Cells were cultured in serum-free medium (GE Healthcare Life Sciences, Logan, UT, USA) at 37˚C overnight and pretreated with 100 nM apelin for 2 h, followed by treatment with 50 ng/ml resistin for 1 or 48 h.…”
Section: Introductionmentioning
confidence: 99%